Pemodelan Biaya Reverse Logistics Pada Pengelolaan Kemasan Minyak Goreng - Rahmi Ramadhany; Rika Ampuh Hadiguna; Ahmad Syafruddin Indrapriyatna; Suci Oktri Viarani (Politeknik ATI Padang, 2023)
Indonesia is listed as the second largest contributor to plastic waste in the world. The problem currently faced is the increasing amount of plastic waste which is one result of the business processes of companies using plastic packaging or plastic packaging manufacturers, one of the plastic packaging waste that comes from cooking oil packaging. The method to solve the problem of processing cooking oil packaging waste carried out in this study is to modify the existing system into a reverse logistics system. Currently, cooking oil companies have not implemented reverse logistics to reduce plastic packaging production. The reverse logistics system applied in this study is to modify cooking oil packages into packages that can be used repeatedly. The reverse logistics system that is applied is then modeled linerly to find out the minimal costs in implementing reverse logistics for the packaged cooking oil. Based on the development of the packaged cooking oil waste management model, it is known that the results of determining the model solution with the linear programming model are the minimal costs for reverse logistics of packaged cooking oil. The model is designed to do a sensitivity analysis by making changes to the reverse logistics cost parameters, changes in the reverse logistics cost parameters resulting in changes to the results that are directly proportional. The designed model is implemented using PT. XYZ which has a similarity with the designed system.